“Panengen” Indigenous Knowledge as the Financial Behavior of Cikalong Community - Nurul Azizah; Sulaeman Rahman Nidar; Kurniawan Saefullah (ijd-demos, 2022)
AbstractThis study aims to examine the panengen culture, an indigenous knowledge as the basis of the financial management of the Cikalong community. This study uses a qualitative method with a case study approach, which analyzes data based on in-depth interviews, non-participatory observations, and documentation about the panengen culture in the financial management of the Cikalong community. The results of this study show that the financial management process of the Cikalong community is based on the cultural concepts of panengen such as basajan, pamali, and neundeun miraweuy which shape their financial behavior.Keywords: Panengen culture, Financial Behavior, Financial Literacy AbstrakPenelitian ini bertujuan untuk mengkaji mengenai budaya panengen yang menjadi indigenous knowledge sebagai dasar pengetahuan dalam pengelolaan keuangan masyarakat Desa Cikalong. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus, dimana data yang dianalisis berdasarkan data dari wawancara mendalam, observasi non partisipatoris, dan dokumentasi berkaitan dengan budaya panengen dalam pengelolaan keuangan masyarkat Desa Cikalong. Hasil dalam penelitian ini menunjukan proses pengelolaan keuangan masyarakat Desa Cikalong berlandaskan dari konsep-konsep budaya panengen yaitu basajan, pamali dan neundeun miraweuy yang membentuk financial behavior mereka.Kata Kunci: Budaya Panengen, Financial Behavior, Financial Literacy